Diurnally Fluctuating pCO2 Modifies the Physiological Responses of Coral Recruits Under Ocean Acidification - Jiang, Lei; Guo, Ya-Juan; Zhang, Fang; Zhang, Yu-Yang; McCook, Laurence John; Yuan, Xiang-Cheng; Lei, Xin-Ming; Zhou, Guo-Wei; Guo, Ming-Lan; Cai, Lin; Lian, Jian-Sheng; Qian, Pei-Yuan; et al. (Frontiers in Physiology, 2019)
Diurnal pCO2 fluctuations have the potential to modulate the biological impact of ocean acidification (OA) on reef calcifiers, yet little is known about the physiological and biochemical responses of scleractinian corals to fluctuating carbonate chemistry under OA. Here, we exposed newly settled Pocillopora damicornis for 7 days to ambient pCO2, steady and elevated pCO2 (stable OA) and diurnally fluctuating pCO2 under future OA scenario (fluctuating OA). We measured the photo-physiology, growth (lateral growth, budding and calcification), oxidative stress and activities of carbonic anhydrase (CA), Ca-ATPase and Mg-ATPase. Results showed that while OA enhanced the photochemical performance of in hospite symbionts, it also increased catalase activity and lipid peroxidation. Furthermore, both OA treatments altered the activities of host and symbiont CA, suggesting functional changes in the uptake of dissolved inorganic carbon (DIC) for photosynthesis and calcification. Most importantly, only the fluctuating OA treatment resulted in a slight drop in calcification with concurrent up-regulation of Ca-ATPase and Mg-ATPase, implying increased energy expenditure on calcification. Consequently, asexual budding rates decreased by 50% under fluctuating OA. These results suggest that diel pCO2 oscillations could modify the physiological responses and potentially alter the energy budget of coral recruits to future OA, and that fluctuating OA is more energetically expensive for the maintenance of coral recruits than stable OA.